ผลของกระบวนการแปรรูปด้วยความดันสูงต่อคุณภาพของเนื้อไก่สด - ธัชนนท์ ชิตสกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research aimed to study the effect of high pressure processing on destruction of S. Typhimurium, eating quality and structure of fresh chicken breast meat. The first part of the research was to determine optimum conditions to destroy 2-3 log cfu/g of S. Typhimurium within 10 minutes. Approximately 107 cfu/g of S. Typhimurium was inoculated onto the surface of the fresh meat samples. The samples were treated with high pressure at 200 - 400 MPa, 25 - 35 oC, for 0.5-20 min. The results showed that, at constant pressure and temperature, time-dependent inactivation of S. Typhimurium followed pseudo first-order kinetic. Increasing pressure and/or temperature led to decreasing decimal reduction time (D) values. D value of the treatment at 400 MPa, 35 oC was 0.25 min. The temperature resistance of S. Typhimurium at constant pressure was considered from ZT value. When pressure increased from 200 MPa to 400 MPa, ZT increased from 7.91 to 84.75 oC. The pressure resistance of S. Typhimurium at constant temperature was shown by Zp value. When temperature increased from 25 to 35 oC, Zp increased from 93.46 MPa to 200.00 MPa The processing conditions of 300 MPa, 35 oC, 1 minute and 400 MPa, 30 oC, 1 minute, which led to 2.34 log cfu/g and 3.92 log cfu/g reduction of S. Typhimurium, respectively, were selected for further studies. The second part of the study was to evaluate the eating quality based on color in CIELAB system, water-holding capacity (WHC), cooking loss (CL), shear force (SF) using the Texture Analyzer. Structure of the meat samples was also determined. The results showed that the treatment at higher pressure resulted in significant increase in the L* values of fresh chicken meat (p≤0.05) and increase in color difference (∆E) compared to the control. But L*, a* and b* values of the pressurised and cooked chicken meat was not significantly (p>0.05) different from those of the cooked meat prepared from the control sample. The treatment at higher pressure resulted in significant decrease in the WHC and significant increase in the CL (p≤0.05). High pressure treatment did not cause significant change in SF of fresh chicken meat (p>0.05). However, SF of the pressurised and cooked chicken meat increased significantly (p≤0.05) comparing to those of the cooked meat prepared from the control sample. Structural determination by scanning electron microscope showed that the treatment at higher pressure resulted in greater extent of protein denaturation/ coagulation on surface of the chicken meat and the contraction of the muscle bundles, led to apparent separation of the muscle bundles from the connective tissues.